When is “convenient time” for residents?: a trial of Resident Study Log as asynchronous learning tool for residents - Tadayuki Hashimoto; Shoko Ariyoshi; Taira Ariyoshi; Ryosuke Horitani; Mohammad Adrian Hasdianda; Kanapa Kornsawad; Shunsuke Kosugi; Makoto Kikukawa; Tomio Suzuki (Medical Education Online)
Introduction The integration of online learning in health professions education has grown rapidly, offering flexibility to learners worldwide. Asynchronous online learning allows residents to engage with educational content at a time convenient for them, accommodating their demanding schedules. This study aims to reveal how residents approach asynchronous online learning during their residency training.Methods The Resident Study Log, an asynchronous learning tool, was introduced in a teaching hospital in Japan. This tool facilitated residents to share daily reflections on their learning experiences, allowing supervising physicians outside of their regular clinical teams to provide feedback. Posts shared between April 2020 and July 2021 were reviewed. The outcome measured included the frequency and timing of posts as well as residents’ satisfaction and perceived burden, which were assessed through anonymous surveys.Results A total of 31 residents participated during the study period, posting 599 entries on the Resident Study Log, averaging one post per resident every two days. Participants reported an average satisfaction score of 5.3 out of 6.0 (6-point Likert scale, where 1 indicated ‘not satisfied at all’ and 6 indicated ‘very satisfied’), while the perceived burden averaged 4.0 out of 6.0 (6-point Likert scale, where 1 indicated ‘not burdensome at all’ and 6 indicated ‘very burdensome’). Notably, posting activity peaked at around 23:00, with 17.4% of posts created between midnight and 5:00.Conclusion The Resident Study Log was a simple, low-cost tool, with high satisfaction levels among residents. However, the late-night posting pattern raises concerns about resident well-being and sleep hygiene. As asynchronous learning is increasingly more prevalent, it is crucial to ensure it does not inadvertently impose hidden burdens on learners’ overall well-being.